Different Dimensions of Borderlines in War Situations. Once Again on Vinko Brešan’s Witnesses - Boguska, Anna (Poznańskie Studia Slawistyczne, 2025)
The authoress offers an overview of various dimensions of borderlines in relation to the war situation, based on the analysis of Witnesses by Vinko Brešan (2003), a film that went down in the history of Croatian cinematography as the first to address the issue of Croatian war crimes. Starting in her reflection from the figure of Barić, i.e. one of the killers of a Serbian civilian, but also a soldier-suicide, she introduces Jaspers’ concept of guilt as a fundamental limit situation, which in this case is the result of the crimes committed. In further reflection, she reads the self-destructive act of the protagonist through the categories of a political manifesto (Banu Bargu), to state that the protagonist personifies the director himself, i.e. the one whose activity has political significance in the spirit of Jacques Rancière’s thought, because it consists in shifting the boundaries of visibility in the Croatian world.